Pengaruh Peran Serikat Pekerja dan Kompensasi Terhadap Kesejahteraan Buruh Wanita - Geby Alvita; Ari Pradhanawati; Reni Shinta Dewi (Universitas Diponegoro, 2015)
Excerpted from The World Factbook of data released by the Central Intelligence Agency (CIA) in 2013, Indonesia is the fifth largest force among the countries with calculations 118.1 million people in 2012. According to data from ILO (International Labour Organization) to Indonesia in 2013, as many as 52% of the Indonesian labor is dominated by women. Economic factors are the main reasons women choose to be workers. This condition then made the woman labors want the welfare given by the company to be maximum and fulfilled. The factors that support the well-being of labors among others is the role of unions labor and compensation. Through the union labor they sent their aspirations so the role of union labor is very important to specify the welfare of women labors. In addition, compensation is also important for the labors as individuals because of the amount of compensation reflects the size of their work among the workers themselves. The purpose of this study was to determine the influence of union labor’s role and compensation for the welfare of women workers PT. Hanil Indonesia. This research type is explanatory research. The population in this study were female workers of PT. Hanil Indonesia and the number of samples taken were 95 respondents. The sampling technique used is theSlovin formula. The analytical method used is the correlation coefficient, coefficient of determination, simple linear regression, multiple linear regression, T test and F test with SPSS version 16. Research results through coefficient determination analysis shows that the role of union labor and compensation has a positive and significant effect on the woman labors welfare partially (with results respectively 30.5% and 43.9%) and simultaneously 54.4% for the woman labors welfare. Based on the results, it can be concluded that the role of union labors in PT. Hanil Indonesia is good, besides the compensation is important in supporting their welfare. The advice given in this study is the union labors should be more responsive and quick in responding to complaints of labors as well as the company further improve the welfare of women laborsthrough the compensation.